2015
DOI: 10.1093/jee/tov186
|View full text |Cite
|
Sign up to set email alerts
|

Two Chitin Biosynthesis Pathway Genes inBactrocera dorsalis(Diptera: Tephritidae): Molecular Characteristics, Expression Patterns, and Roles in Larval–Pupal Transition

Abstract: Glucose-6-phosphate isomerase (G6PI) and UDP-N-acetylglucosamine pyrophosphorylase (UAP), two key components in the chitin biosynthesis pathway, are critical for insect growth and metamorphosis. In this study, we identified the genes BdG6PI and BdUAP from the oriental fruit fly, Bactrocera dorsalis (Hendel). The open reading frames (ORFs) of BdG6PI (1,491 bp) and BdUAP (1,677 bp) encoded 496 and 558 amino acid residues, respectively. Multiple sequence alignments showed that BdG6PI and BdUAP had high amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…When the S. exigua TRE1 and TRE2 genes were suppressed, G6PI , UNAP , CHSA ( CHS1 ) and CHSB ( CHS2 ) gene expression decreased, indicating that TRE genes can regulate chitin synthesis . In addition, the expression of both G6PI and UAP was significantly upregulated by 20‐hydroxyecdysone . Our results showed that expression of all TRE genes except TRE1‐1 increased in the dsNLTPS2 injection treatment, whereas HK and G6PI2 gene expression decreased 72 h after dsNLTPS2 injection (Figs D and F), which is similar to the results of S. exigua TRE gene inhibition .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…When the S. exigua TRE1 and TRE2 genes were suppressed, G6PI , UNAP , CHSA ( CHS1 ) and CHSB ( CHS2 ) gene expression decreased, indicating that TRE genes can regulate chitin synthesis . In addition, the expression of both G6PI and UAP was significantly upregulated by 20‐hydroxyecdysone . Our results showed that expression of all TRE genes except TRE1‐1 increased in the dsNLTPS2 injection treatment, whereas HK and G6PI2 gene expression decreased 72 h after dsNLTPS2 injection (Figs D and F), which is similar to the results of S. exigua TRE gene inhibition .…”
Section: Discussionmentioning
confidence: 71%
“…These rates were 42 and 38% when TRE1‐4 and TRE2 genes were inhibited by RNAi, respectively, in T. castaneum (unpublished work). Additionally, RNAi silencing of UAP resulted in 65% mortality and abnormal phenotypes of larvae, whereas RNAi silencing of BdG6PI had a slight effect on insect moulting in Bactrocera dorsalis …”
Section: Discussionmentioning
confidence: 99%
“…However, the silencing of different genes leads to different rates of insects with phenotypic deformities and mortality rates. For example, the silencing of CHS in S. exigua leads to 50% abnormal phenotypes 69 and 37.27% mortality 66 , the silencing of UAP in Bactrocera dorsalis leads to 65% abnormal phenotypes 70 , and the silencing of Cht1 , Cht5 , Cht7 , Cht9 , and Cht10 in N. lugen leads to 50% mortality 36 . Mortality rates can reach up to 57% after the injection of 1μg of validamycin to N. lugen larvae (unpublished data), confirming that the application of TRE inhibitors can be a promising tool for pest control 20 .…”
Section: Discussionmentioning
confidence: 99%
“…UAPs have been well studied in bacteria, fungi, and human, and their X-ray crystal structures were made available [10], but no crystal structure of insect UAPs were determined. Nevertheless, molecular cloning and gene expression studies were performed and sequences were made available for some insect UAPs [12,13]. To assess the significance of UAP during the growth and development, mutation studies were performed in Drosophila melanogaster UAP (DmUAP) that resulted in deformities in the cuticle, tracheal tube morphogenesis, and central nervous system fasciculation.…”
Section: Introductionmentioning
confidence: 99%